Covert narrative capacity: Mental life in patients thought to lack consciousness. Issue 1 (14th December 2016) - Naci, Lorina; Graham, Mackenzie; Owen, Adrian M.; Weijer, Charles
Abstract: Despite the apparent absence of external signs of consciousness, a significant proportion of behaviorally nonresponsive patients can respond to commands by willfully modulating their brain activity. However, little is known about the mental life of these patients. We discuss a recent innovative approach, which sheds light on the preserved cognitive capacities of these patients, including executive function, theory of mind, and the experience of affective states. This research represents a fundamental shift in our understanding of these patients, and has important implications for both their continued treatment and care. Moreover, this research marks out avenues for future inquiry into the residual cognitive capacities of these patients.